Designing a Surveillance System to Monitor the Adverse Health Effect of Environmental Disasters: A Case Study of Drying Lake Urmia-Iran - Hojatolah Gharaee; Rebecca Susan Dewey; Ramin Rezapour; Naser Derakhshani; Saber Azami-aghdash (SAGE Publishing, 2022)
Background Through designing a surveillance system, steps to policy making and designing measures needed to reduce the potential risks of environmental disasters on human health could be taken. Therefore, this study aimed to develop a model for Environmental Disasters Diseases Surveillance System (EDDS) to monitor Adverse Health Effects (AHEs) of Environmental Disasters (AHEEDs). Methods As the first step, the literature review was conducted to identify the AHEEDs. Then, using the results of the first step and analyzing the existing documents, the AHEEDs were identified, and, based on the experts' opinions, high-priority effects were included in the EDDS. Then, using semi-structured interviews, 20 experts' views on the appropriate model of EDDS were investigated. To design the initial model, a panel of experts was formed with six participants. Finally, the Delphi technique was used for expert opinion and model finalization. Results As a result of the literature review and document analysis, 41 hazards/diseases were identified. Finally, ten diseases were suggested to enter the EDDS. In the experts' view, it is better that communicable diseases be reported actively and urgently and Non-Communicable Diseases (NCD) actively and non-urgently. From the participants' point of view, the most significant achievements of the EDDS can be organizational and managerial, health promotion, and economic achievements. Conclusion Developing a dedicated EDDS for AHEEDs can be very helpful for better management of these effects. To this end, the model proposed in this study can serve as a guide for national and local policymakers to implement surveillance systems for AHEEDs.